Impact of intestinal microbiota on metabolic toxicity and potential detoxification of amygdalin - Wen, Qiuyu; Yu, Shen; Wang, Shanshan; Qin, Yan; Xia, Quan; Wang, Sheng; Chen, Guanjun; Shen, Chenlin; Song, Shuai (Frontiers in Microbiology, 2022)
Amygdalin is metabolized into cyanide in vivo, which may lead to fatal poisoning after oral administration. The defense mechanisms against toxic cyanide have not yet been adequately studied. In this study, comparative toxicokinetics study of amygdalin was performed in normal and pseudo germ-free rats. The efficiency of cyanide release was significant higher in normal group while given a single oral dose of 440 mg/kg (50% median lethal dose). Thiocyanate, the detoxification metabolite, was firstly detected in feces, caecum, and intestinal microbiota incubation enzymic system. The results suggest intestinal microbiota is involved in bidirectional regulation of toxicity and detoxification of amygdalin. We further identified the species related to cyanogenesis of amygdalin with metagenomic sequencing, such as Bifidobacterium_pseudolongum, Marvinbryantia_formatexigens, and Bacteroides_fragilis, etc. Functional analysis of microbiota reveals the detoxification potential of intestinal microbiota for cyanide, in which sulfurtransferase superfamily, including rhodanese, are the main detoxification enzymes, largely present in Coriobacteriaceae_bacterium, Butyricicoccus_porcorum, and Akkermansia_muciniphila, etc. Besides, cyanoamino acid metabolism pathway dominated by Escherichia coli may contribute to the detoxification metabolism of cyanide. In summary, intestinal microbiota is the first line of defense against the toxicity induced by amygdalin.